Clinical Characteristics and Prognosis of Acute Myeloid Leukemia Patients with Protein Tyrosine Phosphatase Non-Receptor Type 11 Gene Mutation - Huang R; Zhang YT; Lin Y; Pang RL; Yang Z; Zhao WH (Dove Medical Press, 2023)
Rui Huang,* Yi-Ting Zhang,* Yu Lin, Ru-Li Pang, Zhi Yang, Wei-Hua Zhao Department of Hematology, the First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei-Hua Zhao, Department of Hematology, the First Affiliated Hospital of Guangxi Medical University, Shuang-Yong Road 6, Nanning, Guangxi Zhuang Autonomous Region, People's Republic of China, Tel +86-771-5356746, Fax +86-771-5352681, Email zhaowh21@163.comObjective: The purpose of our study was to investigate the clinical characteristics, molecular biological characteristics and prognosis of acute myeloid leukemia (AML) patients with protein tyrosine phosphatase non-receptor type 11 (PTPN11) gene mutation.Methods: The clinical data of 30 newly diagnosed adult AML patients with PTPN11 gene mutation were analyzed retrospectively. Kaplan-Meier and Cox proportional risk regression model were examined for prognostic analysis and prognostic factor screening.Results: High-frequency mutation sites of PTPN11 gene are located in exon 3 of chromosome 12, which are D61 and A72 (16.7%), followed by E76 (13.3%). The median variant allele frequency (VAF) of PTPN11 mutant gene is 18.4%. The patients were divided into two groups according to PTPN11 VAF 35.3% (upper quartile). We observed that the peripheral blood leukocyte count in patients with VAF ≥ 35.3% was significantly higher than patients with VAF < 35.3% (p = 0.019) and also closely related to M5 (p = 0.016) and internal tandem duplication (ITD) of FMS-like tyrosine kinase 3 (FLT3) (FLT3-ITD) mutation (p = 0.048). Taking PTPN11 VAF 20% and 35.3% as the cutoff value, the patients were divided into two groups, and the overall survival and event-free survival (EFS) of the two groups were not significant. Multivariate analysis of Cox risk ratio model showed that white blood cell count and Eastern Cooperative Oncology Group (ECOG) physical status score were independent risk factors affecting the EFS.Conclusion: Our study observed that PTPN11 VAF may not be a prognostic factor in patients with PTPN11mut AML. Newly diagnosed high white blood cell count and poor performance status were independent risk factors for EFS in PTPN11mut AML. Keywords: acute myeloid leukemia, PTPN11, mutation, clinical characteristics, prognosis